The Comorbidities And Clinical Profile Of Chronic Obstructive Lung Disease Patients Attending Tertiary Care Hospital - Sumathi, Dr.Matta; Vani, P.; Babitha, B.; Basha, V.Wazeed; Kumar, I Naveen (Asian Journal of Pharmaceutical Research and Development, 2022)
Background: Chronic pulmonary obstructive disease (COPD) has been responsible for the decreased quality of life as well as increased morbidity and mortality. The objective of the present study was to observe the comorbidities and clinical profile of patients with chronic pulmonary obstructive disease at a tertiary care center. Methods: The data were collected from 80 COPD patients presenting to OPD of the pulmonary medicine department from August 2021 to January 2022. The data were extracted from a medical case sheet and for statistical analysis, MS Excel was used. Results: As the age increased the prevalence of COPD increased and the highest was found to be in the age group above 60 years of age. Males were more affected by COPD as compared with females. The smokers were more compared to the nonsmokers. The prevalence of smoking among COPD was noted to be 60% compared to 40% as non-smokers. The most common clinical feature was breathlessness 100% followed by cough 95%. 15% of the cases of copdhad Hypertension as the comorbidity. Conclusion: Breathlessness was the most common symptom at presentation and hypertension were the most common co-morbidities found.